A Study on the Awareness of Dental Hygienists on Maternity Protection and Work-Family Balance Assistance Policy - Seon-Hui Kwak; Bo-Mi Shin; Soo-Myoung Bae (The Korean Society of Dental Hygiene Science, 2023)
Background: This study investigated the awareness and utilization of maternity protection and work-family balance support policies among dental hygienists in dental hospitals and clinics.Methods: We surveyed 200 dental hygienists. Twenty-two who did not meet the inclusion criteria were excluded, leaving 178 participants for analysis. The self-administered 48-item questionnaire gathered information on demographics, workplace details, policy awareness, government knowledge, and suggestions for improvement. Results: Awareness of maternity and family support programs significantly differed with age, marital status, number of children, and clinical experience. Dental hygienists in general hospitals and university hospitals reported greater ease of utilizing these policies compared to those in dental clinics. Among the participants, 27.7% took pre- and post-maternity leave, 26.6% took parental leave, 16.9% had reduced working hours during pregnancy, 15.8% had reduced working hours during childhood,and 8.5% during family leave. To promote program uptake, participants suggested mandatory implementation across workplaces (68.4%), expanded support for substitute workers (48.6%), and increased education and promotion of government support (42.4%). Conclusion: While most dental hygienists were aware of the Maternity Protection and Work-Family Balance Assistance Policy, utilizing it proved challenging due to several factors. Organizational policies or practices may not fully implement this policy, while workplace culture could discourage its use. Unfair treatment and the lack of available substitutes further hindered access. To prevent career interruptions for dental hygienists due to pregnancy, childbirth, childcare, and family care, and to maintain career continuity, the dental community and government should establish a multifaceted social support system. This system should prioritize several key areas: strengthening policy promotion, fostering a family-friendly atmosphere, improving management and supervision of policy implementation and developing a robust support system for substitute personnel.